2000
DOI: 10.1074/jbc.m002226200
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Inhibits Long Term Potentiation in the Rat Dentate Gyrus by Activating Caspase-1

Abstract: Lipopolysaccharide, a component of the cell wall of Gram-negative bacteria, may be responsible for at least some of the pathophysiological sequelae of bacterial infections, probably by inducing an increase in interleukin-1␤ (IL-1␤) concentration. We report that intraperitoneal injection of lipopolysaccharide increased hippocampal caspase-1 activity and IL-1␤ concentration; these changes were associated with increased activity of the stress-activated kinase c-Jun NH 2 -terminal kinase, decreased glutamate relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
158
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(184 citation statements)
references
References 55 publications
(59 reference statements)
25
158
1
Order By: Relevance
“…This treatment caused increased numbers of microglia with phagocytotic activity (Iba1 ϩ /ED1 ϩ ) in the SGZ/ GCL, both at the time when the new cells were born (1 week after LPS injection) and when they had reached the mature state (at the time of recording and morphological analysis, 7 weeks later). Consistent with our findings, Herber et al (2006) potentiation (Vereker et al, 2000;Hennigan et al, 2007). Furthermore, injection of LPS in the hippocampal CA1 area of rats gives rise to learning and memory deficits and decreased glutamatergic neurotransmission but no cell death (Tanaka et al, 2006).…”
Section: Discussionsupporting
confidence: 77%
“…This treatment caused increased numbers of microglia with phagocytotic activity (Iba1 ϩ /ED1 ϩ ) in the SGZ/ GCL, both at the time when the new cells were born (1 week after LPS injection) and when they had reached the mature state (at the time of recording and morphological analysis, 7 weeks later). Consistent with our findings, Herber et al (2006) potentiation (Vereker et al, 2000;Hennigan et al, 2007). Furthermore, injection of LPS in the hippocampal CA1 area of rats gives rise to learning and memory deficits and decreased glutamatergic neurotransmission but no cell death (Tanaka et al, 2006).…”
Section: Discussionsupporting
confidence: 77%
“…4), and this finding is supported by data from several experiments that were conducted in vitro and that revealed that application of IL-1␤ to hippocampal slices inhibited LTP in dentate gyrus (118), CA1 (54), and CA3 (279). Consistently, LTP has been shown to be impaired in several circumstances in which IL-1␤ concentration in hippocampus is increased, for example, in aged (380,442,441,627) and stressed (442,629) rats, rats treated with LPS (627), and rats exposed to ␥-irradiation (A. M. Lynch, M. Moore, S. Craig, P. E. Lonergan, and M. A. Lynch, unpublished data; see Fig. 5).…”
Section: Il-1␤ Ltp Learning and Memorysupporting
confidence: 72%
“…4) arising from an increase in SOD activity in the absence of concomitant changes in activities of glutathione peroxidase or catalase (87,191,466,467). Increased ROS accumulation is closely coupled with increased concentration of IL-1␤, and these changes have been correlated with deficits in LTP in the aged animal (400,441,442,467,627,628). The consequences of a chronic increase in ROS production are profound and lead to lipid peroxidation, which in turn results in a decrease in the membrane concentration of polyunsaturated fatty acids, altering membrane fluidity (353,355,441,443).…”
Section: Age Ltp Learning and Memorymentioning
confidence: 99%
“…This may explain the enhanced LTP and diminished DSI in LPS-treated and COX-2 transgenic mice we observed in the present study. Of note however are studies indicating that LPS inhibits LTP in the rat dentate gyrus (Vereker et al, 2000). The discrepancy between our observations and these is not clear, but may be due to differences in doses used (3 mg/kg versus 0.2 mg/kg) and in the methods used to record (ex-vivo slices versus in vivo).…”
Section: Discussioncontrasting
confidence: 53%